Metal titanium compound photoresist composition and preparation method, patterning method and application thereof
By using metal titanium oxide clusters and metal titanium oxide nanoparticles in photoresist, combining metal titanium alkoxide with benzoic acid or its derivatives, the problem of insufficient performance of existing photoresist is solved, and a photoresist composition with high sensitivity, resolution and stability is achieved, improving the accuracy and efficiency of photolithography technology.
Patent Information
- Application Number
- CN202411850983.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
AI Technical Summary
The polymer resin monomers in existing photoresists have problems such as inconsistent molecular weight and molecular formula, insufficient etch resistance, poor thermal stability, poor chemical stability, poor mechanical properties, poor development performance and poor environmental adaptability, which limits the accuracy and efficiency of lithography technology.
A photoresist composition based on metal titanium oxide clusters and metal titanium oxide nanoparticles is prepared by combining metal titanium alkoxide with benzoic acid or its derivatives to form titanium oxide nanoparticles and mixing them with organic solvents.
It significantly improves the sensitivity, resolution, thermal stability, chemical stability, mechanical properties and development properties of photoresist, simplifies the preparation process, reduces production costs, and improves environmental adaptability and reliability.
Smart Images

Figure CN119620538A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoresists, and in particular to a photoresist composition and a patterning method thereof. Background Art
[0002] With the rapid development of micro-nano processing technology, photoresist, as the core material in this field, plays a vital role in promoting the progress of the entire industry. As a key means to achieve photoresist patterning, the diversity of photolithography technology (including g-line, i-line, KrF, ArF, electron beam, extreme ultraviolet and other lithography methods) provides flexible choices for different application scenarios. However, the polymer resin monomers widely used in traditional photoresists have the following defects:
[0003] Inconsistent molecular weight and molecular formula: results in poor repeatability of the photoresist and difficulty in achieving consistent performance.
[0004] Insufficient etching resistance: It is easily corroded during the etching process, affecting the integrity and accuracy of the pattern.
[0005] Poor thermal stability: prone to decomposition or deformation under high temperature conditions, resulting in defects during patterning.
[0006] Poor chemical stability: The stability is poor in certain chemical environments (such as strong acids, strong bases or organic solvents), and chemical reactions are prone to occur, resulting in the performance degradation or failure of the photoresist.
[0007] Poor mechanical properties: It is easy to break or fall off during mechanical processing (such as etching, peeling, etc.), affecting the integrity and accuracy of the pattern.
[0008] Poor development performance: During the development process, the solubility difference between the exposed area and the non-exposed area is not obvious, resulting in poor development effect and blurred pattern edges.
[0009] Poor environmental adaptability: The performance under different environmental conditions (such as temperature and humidity changes) fluctuates greatly, affecting its stability and reliability in practical applications.
[0010] Complex preparation: The preparation process of traditional photoresists is complex, requiring multiple steps and strict condition control, which increases production costs and process difficulty. These problems limit the accuracy and efficiency of photolithography technology.
[0011] In order to overcome the limitations of polymer resins, researchers have turned their attention to metal oxygen clusters and metal oxide nanoparticles. These materials have shown great potential for use in photoresists due to their unique physical and chemical properties, such as highly uniform molecular structure, excellent etching resistance and good optical properties. Metal oxygen clusters can not only significantly improve the resolution and stability of photoresists, but also optimize the processing technology to a certain extent and reduce production costs.
[0012] Although metal oxide clusters have made significant progress in improving the performance of photoresists, the problem of insufficient sensitivity still needs to be solved. Especially in the field of high-precision processing such as visible light, ultraviolet light, electron beam and extreme ultraviolet lithography, the sensitivity of metal oxide clusters has become a key factor restricting their widespread application. Low sensitivity not only leads to blurring and distortion of lithographic patterns, but also increases uncertainty and scrap rate in the processing process, thus affecting product quality and production efficiency.
[0013] In order to improve the sensitivity of metal oxoclusters, researchers have explored a variety of methods. Among them, adding thiols to achieve thiol-ene click reactions is an effective strategy. By introducing specific functional groups, the interaction between metal oxoclusters and other components of the photoresist is enhanced, thereby improving the overall photosensitivity. However, this method has limited effect in improving the sensitivity of metal oxoclusters and metal oxide nanoparticles patterned under long-wavelength light sources (>365nm), and may also bring about problems such as strong odor, complex reaction conditions, and increased control difficulty.
[0014] Therefore, there is an urgent need to develop a new type of photoresist composition that can effectively overcome the deficiencies in the prior art, improve the sensitivity, resolution, thermal stability, chemical stability, mechanical properties and developing performance of the photoresist, while simplifying the preparation process, reducing costs and improving environmental adaptability. Summary of the invention
[0015] The present invention is based on the needs of the background technology and proposes a photoresist composition based on metal titanium oxide clusters and metal titanium oxide nanoparticles (hereinafter referred to as titanium oxide compound nanoparticles) and a preparation method and patterning method thereof, aiming to provide high-performance solutions for micro-nano manufacturing, semiconductor production and optical devices, and even biomedicine and other fields.
[0016] Firstly, the present invention discloses a photoresist composition, which comprises an organic solvent and titanium oxide nanoparticles, wherein the weight ratio of the titanium oxide nanoparticles in the composition is 1-30wt%, the weight ratio of the organic solvent in the composition is 70-99wt%, and the titanium oxide nanoparticles are formed by combining metal titanium alkoxide and benzoic acid or its derivatives.
[0017] For the photoresist composition described above, it is further preferred that: the weight ratio of the titanium oxide compound nanoparticles in the composition is 1-20 wt %; the weight ratio of the organic solvent in the composition is 80-99 wt %.
[0018] For the photoresist composition described above, it is further preferred that: the weight ratio of the titanium oxide compound nanoparticles in the composition is 2.5-15 wt %; the weight ratio of the organic solvent in the composition is 87.5-99 wt %.
[0019] For the photoresist composition described above, it is further preferred that the structural formula of the titanium oxide compound nanoparticles is as shown in general formula I, wherein:
[0020] R' to R""" are each independently selected from one of n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, isopentyl and neopentyl;
[0021] R1-R5 is determined by the addition of benzoic acid or its derivatives during the preparation process; R1, R2, R3, R4, R5 are each independently selected from hydrogen, nitro, halogen, a hydrocarbon group having 1-8 carbon atoms, or a hydrocarbon group having 1-8 carbon atoms substituted by a hydrocarbonoxy group, a hydrocarbonamino group, or a dihydrocarbylamino group:
[0022]
[0023] For the photoresist composition described above, it is further preferred that: the metal titanium alkoxide is selected from one or more of titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, titanium isobutoxide, titanium n-pentoxide, titanium isopentanolate, and titanium neopentoxide;
[0024] For the photoresist composition described above, it is further preferred that the structural formula of the benzoic acid or its derivative is as shown in general formula II:
[0025]
[0026] Wherein, R1, R2, R3, R4, and R5 are each independently selected from one of hydrogen, nitro, halogen, a hydrocarbon group having 1 to 8 carbon atoms, or a hydrocarbon group having 1 to 8 carbon atoms substituted by a hydrocarbonoxy group, a hydrocarbonamino group, or a dihydrocarbylamino group.
[0027] Preferably, R1, R2, R3, R4, and R5 are each independently selected from hydrogen, nitro, halogen, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 6 carbon atoms substituted by halogen, hydrocarbonoxy, hydrocarbonamino, or dihydrocarbylamino.
[0028] More preferably, R1, R2, R3, R4, and R5 are each independently selected from one of hydrogen, nitro, halogen, methyl, monofluoromethyl, difluoromethyl, trifluoromethyl, ethyl, monofluoroethyl, difluoroethyl, trifluoroethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, vinyl, propenyl, allyl, N,N-dimethyl, N,N-diethyl, and N,N-dipropyl.
[0029] For the photoresist composition described above, it is further preferred that: the benzoic acid or its derivative is selected from one of benzoic acid, p-nitrobenzoic acid, p-toluic acid, p-fluorobenzoic acid, p-trifluoromethylbenzoic acid, p-vinylbenzoic acid, p-n-butylbenzoic acid, p-allylbenzoic acid, p-N,N-dimethylbenzoic acid, and m-N,N-dipropylbenzoic acid;
[0030] For the photoresist composition described above, it is further preferred that: the benzoic acid or its derivative is selected from one of the compounds having the following structural formula:
[0031]
[0032]
[0033] For the photoresist composition described above, it is further preferred that the particle size of the titanium oxide nanoparticles is 1 to 3 nm.
[0034] For the photoresist composition described above, it is further preferred that the weight ratio of the metal titanium alkoxide to benzoic acid or its derivative is 1-1.2:1.
[0035] For the photoresist composition described above, it is further preferred that the organic solvent is selected from one or more of toluene, o-xylene, m-xylene, p-xylene, m-trimethylbenzene, propylene glycol methyl ether acetate, propylene glycol methyl ether, chloroform, acetone, cyclopentanone, cyclohexanone, 4-methyl-2-pentanone, 2-heptanone, methanol, ethanol, n-propanol, isopropanol, butyl acetate, ethyl lactate, dimethyl sulfoxide and N,N-dimethylformamide.
[0036] Another aspect of the present invention discloses a method for preparing the above-mentioned photoresist composition, comprising the following steps: (a) dissolving metal titanium alkoxide and benzoic acid or its derivatives in an organic solvent I and mixing them uniformly; (b) reacting the mixture obtained in step (a) at 75-85° C. under an inert atmosphere; (c) cooling to room temperature, separating and drying the solid product to obtain titanium oxide compound nanoparticles, and then dissolving the solid product in an organic solvent to obtain a photoresist composition.
[0037] For the preparation method of the photoresist combination described above, it is further preferred that: in step a, the weight ratio of the metal alkoxide in the mixed solution is 10-20wt%, and the weight ratio of benzoic acid is 10-20wt%; more preferably, the organic solvent I is heptane and tetrahydrofuran, and the weight ratio of heptane to tetrahydrofuran is in the range of 0.6-2.0:1;
[0038] For the preparation method of the photoresist composition described above, it is further preferred that: in step c, the weight ratio of the titanium oxide compound nanoparticles in the composition is 1-30wt%, and the weight ratio of the organic solvent in the composition is 70-99wt%.
[0039] In a third aspect, the present invention discloses a method for patterning the photoresist composition described above, comprising the following steps: applying the photoresist composition on a substrate, and forming a photoresist film by baking or drying at room temperature, and then exposing the photoresist film to photolithography and placing it in a developer to develop and form a photolithography pattern.
[0040] For the patterning method of the photoresist composition described above, it is further preferred that the photolithography exposure method is visible light lithography, electron beam lithography or extreme ultraviolet lithography.
[0041] For the patterning method of the photoresist composition described above, it is further preferred that: the light source of the visible light lithography method is visible light with a wavelength of 365 to 600 nm, and the dosage is 10 to 500 mJ·cm -2 The electron beam lithography method is to expose the electron beam using an electron beam exposure machine, with a dose of 50pC to 50000pC·cm -1 The light source of the EUV lithography method is EUV light with a wavelength of 13.5 nm and a dose of 5 to 500 mJ·cm -2 .
[0042] Finally, the present invention discloses the application of the above-mentioned photoresist composition in the fields of micro-nano manufacturing, semiconductor production, biomedicine, optical devices, etc.
[0043] The present invention has the following beneficial effects:
[0044] 1. In the photoresist composition of the present invention, titanium, which is commonly used as a photocatalytic metal, is used as the central metal, and benzoic acid or its derivatives with a long absorption wavelength and easy to leave are selected as ligands, thereby achieving a significant improvement in photosensitivity. Under the action of extreme ultraviolet light, electron beam and visible light (within the range of 250-600 nanometers), the carboxylic acid ligand is lost or double-bonded.
[0045] Second, the photoinitiator of the present invention can significantly improve the imaging quality and resolution of patterns in UV / visible light lithography, electron beam lithography or extreme ultraviolet lithography. The prepared photoresist exhibits excellent sensitivity in the light source range of 250 nanometers to 600 nanometers, enabling the photoresist to accurately realize photolithographic patterning in this wavelength range, providing a high-performance material foundation and more possibilities for the field of micro-nano manufacturing.
[0046] 3. After the photoresist is exposed, the solubility of the exposed area and the non-exposed area in the developer shows a significant difference. This feature ensures that the photolithography pattern can be accurately formed after the development process, and shows high efficiency in the photolithography process. The feature size of the processed pattern can reach the micro-nano level, meeting the stringent requirements of modern semiconductor and micro-nano manufacturing fields for high-precision patterning.
[0047] The photoresist composition of the present invention exhibits good stability under different environmental conditions (such as temperature and humidity changes), ensuring its reliability and consistency in practical applications, which is particularly important in industrial production and long-term storage.
[0048] The photoresist composition of the present invention adopts common and relatively low-priced raw materials (such as titanium alkoxide and benzoic acid or its derivatives), thereby reducing production costs. Meanwhile, the preparation method is simple, and large-scale production is easy, thereby improving economic benefits.
[0049] The photoresist composition of the present invention has low toxicity of chemical substances involved in the preparation and use process, is environmentally friendly, has simple waste treatment, meets the requirements of modern green chemistry, and reduces pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The XPS graph of O1s of the unexposed film in Example 1 of the present invention is
[0051] Figure 2 This is the XPS graph of O1s of the film after exposure to 254nm light source in Example 1 of the present invention.
[0052] Figure 3 Schematic diagram of the ligand dissociation reaction of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer after exposure in Example 1 of the present invention
[0053] Figure 4 The X-ray powder diffraction pattern of the metal oxide cluster and metal oxide nanoparticle film-forming monomer in Example 1 of the present invention is
[0054] Figure 5 The X-ray powder diffraction pattern of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in Example 2 of the present invention is
[0055] Figure 6 The X-ray powder diffraction pattern of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in Example 3 of the present invention is
[0056] Figure 7 The X-ray powder diffraction pattern of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in Example 4 of the present invention is
[0057] Figure 8 The X-ray powder diffraction pattern of the metal oxide cluster and metal oxide nanoparticle film-forming monomer in Example 5 of the present invention is
[0058] Fig. 9 This is a picture taken with a research upright microscope after the photoresist composition in Example 1 of the present invention is patterned.
[0059] Fig.10 This is a picture taken with a research upright microscope after the photoresist composition in Example 2 of the present invention is patterned.
[0060] Fig.11 This is a picture taken with a research upright microscope after the photoresist composition in Example 3 of the present invention is patterned.
[0061] Fig.12 This is a picture taken with a research upright microscope after the photoresist composition in Example 4 of the present invention is patterned.
[0062] Fig.13 The picture was taken with a research upright microscope after the photoresist composition in Example 5 of the present invention was patterned.
[0063] Fig.14 The picture was taken with a research upright microscope after the photoresist composition in Example 6 of the present invention was patterned.
[0064] Fig.15 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 7 of the present invention is patterned.
[0065] Fig.16 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 8 of the present invention is patterned.
[0066] Fig.17 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 9 of the present invention is patterned.
[0067] Fig.18 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 10 of the present invention is patterned.
[0068] Fig.19 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 1 of the present invention was patterned.
[0069] Fig. 20 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 2 of the present invention was patterned.
[0070] Fig.21 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 3 of the present invention was patterned.
[0071] Fig. 22 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 4 of the present invention was patterned. DETAILED DESCRIPTION
[0072] In order to better understand the technical solution of the present invention, the following is a detailed description through specific examples. These examples are intended to explain the specific application and technical effects of the present invention, but do not limit the scope of protection of the present invention. The materials, equipment and methods involved in all embodiments are conventional choices in the art, unless otherwise specified.
[0073] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0074] Example 1
[0075] Step ①: Take 1g of titanium n-propoxide and 1g of benzoic acid (dissolved in 4g of heptane and 4g of tetrahydrofuran) and add them to a pressure tube, and ultrasonicate for 1 minute. Then, tighten the sample pressure tube cap and seal it with a sealing film. React at 75℃ for 24h, cool to room temperature, pour out the liquid, wash the solid with n-hexane, and dry it at 45℃ in a vacuum environment for 12h. A white solid is obtained, which is a metal titanium oxide cluster and a metal titanium oxide nanoparticle film-forming monomer (titanium oxide compound nanoparticles).
[0076] Step ②: Take 0.1 g of titanium oxide nanoparticles and dissolve them in 2 g of chloroform, stir or ultrasonicate to completely dissolve them, and then filter the photoresist solution twice using a filter membrane with a pore size of 0.22 μm.
[0077] Step 3: Drop the prepared photoresist solution onto the surface of a clean glass substrate and place it in a coating machine at a speed of 400 rpm and an acceleration of 500 rpm s -1 The substrate was then placed under a xenon lamp with a wavelength of 254 nm. When the dose reached 10 mJ·cm -2 , stop exposure. Place the substrate in cyclohexanone for 15 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.
[0078] Example 2
[0079] The process of Example 2 is basically the same as that of Example 1, except that in step ①, 1.5 g of titanium isopropoxide is used for titanium alkoxide, 1 g of p-nitrobenzoic acid, 3.5 g of heptane, and 4 g of tetrahydrofuran are used for the benzoic acid derivative, and the reaction temperature is 80°C. In step ②, 0.7 g of butyl acetate is used as the solvent. In step ③, a quartz plate is used as the substrate, 4000 rpm is used as the rotation speed, and 8000 rpm is used as the acceleration. -1 The exposure dose is 300mJ·cm -2 , methyl isobutyl ketone was selected as the developer, and 20s was selected as the developing time.
[0080] Example 3
[0081] The process of Example 3 is basically the same as that of Example 1, except that in step ①, 1.2 g of n-butoxide titanium is used as the titanium alkoxide, 1.2 g of p-toluic acid, 3 g of heptane, and 4.6 g of tetrahydrofuran are used as the benzoic acid derivative, and the reaction temperature is 85°C. In step ②, 1.2 g of propylene glycol methyl ether acetate is used as the solvent. In step ③, a silicon wafer is used as the substrate, the rotation speed is 6000 rpm, and the acceleration is 12000 rpm s -1 The exposure dose is 500mJ·cm -2 .
[0082] Example 4
[0083] The process of Example 4 is basically the same as that of Example 1, except that in step ①, 1.2 g of titanium isobutylate is used for titanium alkoxide, 1.5 g of p-fluorobenzoic acid, 4.5 g of heptane, and 2.8 g of tetrahydrofuran are used for benzoic acid derivatives. In step ③, the wavelength of the exposure light source is 500 nm, and the exposure dose is 500 mJ·cm -2 , cyclopentanone is used as the developer.
[0084] Example 5
[0085] The process of Example 5 is basically the same as that of Example 1, except that in step ①, 1 g of p-trifluoromethylbenzoic acid is used as the benzoic acid derivative. In step ②, 1.5 g of butyl acetate is used as the solvent. In step ③, a quartz plate is used as the substrate, the rotation speed is 4000 rpm, and the acceleration is 8000 rpm s -1 The exposure light source wavelength is 500nm and the exposure dose is 300mJ·cm -2 , methyl isobutyl ketone was selected as the developer, and 20s was selected as the developing time.
[0086] Example 6
[0087] The process of Example 6 is basically the same as that of Example 1, except that in step ①, 1 g of p-vinylbenzoic acid is used as the benzoic acid derivative. In step ②, 4 g of propylene glycol methyl ether acetate is used as the solvent. In step ③, a silicon wafer is used as the substrate, the rotation speed is 6000 rpm, and the acceleration is 12000 rpm s -1 The exposure light source wavelength is 500nm and the exposure dose is 500mJ·cm -2 , dimethyl sulfoxide is used as the developer.
[0088] Example 7
[0089] The process of Example 7 is basically the same as that of Example 1, except that in step ①, 1 g of p-n-butylbenzoic acid is used as the benzoic acid derivative. In step ③, a silicon wafer is used as the substrate, the rotation speed is 6000 rpm, and the acceleration is 12000 rpm s -1 The exposure method is electron beam exposure, and the exposure dose is 50pC·cm -1 , acetone was used as the developer, 60s was used as the developing time, and a high-resolution scanning electron microscope was used to photograph the exposed pattern.
[0090] Example 8
[0091] The process of Example 8 is basically the same as that of Example 1, except that in step ①, the benzoic acid derivative is 1 g of p-allylbenzoic acid. In step ③, the substrate is a silicon wafer, the rotation speed is 6000 rpm, and the acceleration is 12000 rpm s -1 The exposure method is electron beam exposure, and the exposure dose is 50000pC·cm -1 , the developer was N,N-dimethylformamide, the developing time was 60s, and the exposed pattern was photographed using a high-resolution scanning electron microscope.
[0092] Example 9
[0093] The process of Example 9 is basically the same as that of Example 1, except that in step ①, 1 g of p-N,N-dimethylbenzoic acid is used as the benzoic acid derivative. In step ③, a silicon wafer is used as the substrate, the rotation speed is 6000 rpm, and the acceleration is 12000 rpm s -1 The exposure method is extreme ultraviolet exposure, and the exposure dose is 5mJ·cm -2 , methanol was used as the developer, 60s was used as the developing time, and a high-resolution scanning electron microscope was used to photograph the exposed pattern.
[0094] Example 10
[0095] The process of Example 10 is basically the same as that of Example 1, except that in step ①, the benzoic acid derivative is 1 g of m-N,N-dipropylbenzoic acid. In step ③, the substrate is a silicon wafer, the rotation speed is 6000 rpm, and the acceleration is 12000 rpm s-1 The exposure method is extreme ultraviolet exposure, and the exposure dose is 500mJ·cm -2 , isopropyl alcohol was used as the developer, 60s was used for the developing time, and a high-resolution scanning electron microscope was used to photograph the exposed pattern.
[0096] Comparative Example 1
[0097] The process of Comparative Example 1 is basically the same as that of Example 1, except that in step ①, 1 g of terephthalic acid is used as the benzoic acid derivative. In step ③, a quartz plate is used as the substrate, the rotation speed is 4000 rpm, and the acceleration is 8000 rpm s -1 .
[0098] Comparative Example 2
[0099] The process of Comparative Example 2 is basically the same as that of Example 1, except that in step ①, 1 g of titanium isopropoxide is used as the titanium alkoxide, and 1 g of p-hydroxybenzoic acid is used as the benzoic acid derivative. In step ③, the substrate is a silicon wafer, the rotation speed is 4000 rpm, and the acceleration is 8000 rpm s -1 The exposure dose is 500mJ·cm -2 , methyl isobutyl ketone was selected as the developer, and 20s was selected as the developing time.
[0100] Comparative Example 3
[0101] The process of Comparative Example 3 is basically the same as that of Example 1, except that in step ①, 1 g of titanium alkoxide is used, and 1 g of 1-naphthoic acid is used as the benzoic acid derivative. In step ③, the rotation speed is 4000 rpm, and the acceleration is 8000 rpm s -1 The exposure method is electron beam exposure, and the exposure dose is 50000pC·cm -1 , the developer was N,N-dimethylformamide, the developing time was 60s, and the exposed pattern was photographed using a high-resolution scanning electron microscope.
[0102] Comparative Example 4
[0103] The process of Comparative Example 4 is basically the same as that of Example 1, except that in step ①, 1 g of titanium isobutylate is used as the titanium alkoxide, and 1 g of p-cyanobenzoic acid is used as the benzoic acid derivative. In step ③, a quartz plate is used as the substrate, 4000 rpm is used as the rotation speed, and 8000 rpm is used as the acceleration. -1 The exposure method is extreme ultraviolet exposure, and the exposure dose is 500mJ·cm -2 , isopropyl alcohol was used as the developer, 60s was used for the developing time, and a high-resolution scanning electron microscope was used to photograph the exposed pattern.
[0104] The test conditions of each embodiment and comparative example are shown in Table 1:
[0105] Table 1 List of experimental conditions for each embodiment and comparative example
[0106]
[0107]
[0108] Tests, results and analysis
[0109] Through the simple synthesis experiment described in the embodiment of the present invention, the present invention synthesized 10 molecules and measured the X-ray powder diffraction pattern of the molecules ( Figure 4-Figure 8 ), indicating that titanium oxide nanoparticles were successfully prepared.
[0110] The synthesized photoresist composition was tested for environmental stability, including performance evaluation under different temperature (such as 25°C, 50°C, 80°C) and humidity (such as 30%, 50%, 80%) conditions. The results showed that the photoresist composition exhibited good stability and consistency under various environmental conditions, ensuring its reliability and durability in practical applications.
[0111] The synthesized photoresist composition was tested for chemical stability, including stability evaluation in strong acids (such as HCl), strong bases (such as NaOH) and organic solvents (such as acetone and ethanol). The results showed that the photoresist composition still maintained good performance in these chemical environments without obvious degradation or performance decline.
[0112] The synthesized photoresist composition was tested for its development performance, including the evaluation of the development effect in different developers (such as cyclohexanone, methyl isobutyl ketone, and acetone). The results showed that during the development process, the solubility difference between the exposed area and the non-exposed area of the photoresist composition was obvious, and clear and sharp pattern edges could be formed.
[0113] The preparation process of the synthesized photoresist composition was repeatedly tested, and the results showed that the preparation method has high repeatability and stability. In addition, a small-scale batch production test was also carried out to verify the feasibility and economy of the method in industrial production.
[0114] The photoresist composition of the present invention was compared with several existing polymer resin photoresists on the market in terms of sensitivity, resolution, thermal stability, chemical stability, mechanical properties, and developing properties. The results showed that the photoresist composition of the present invention showed significant advantages in all test items, and had higher performance and wider application prospects.
[0115] Taking Example 1 as an example, the film after exposure to a 254 nm light source was analyzed by X-ray photoelectron spectroscopy (XPS) to explore the exposure reaction mechanism. Figure 1 and Figure 2 As shown in the figure, after the film is exposed, the carbon-oxygen double bond is reduced, indicating that the carbon-oxygen double bond is reduced. The oxygen-titanium single bond content is reduced, indicating that the carboxylic acid and butoxy ligands are dissociated from the central metal structure. The schematic diagram of the inferred reaction mechanism is shown in the figure.
[0116] Subsequently, an exposure experiment was conducted. First, the spin-coated film was exposed to 254nm and 500nm light sources respectively, and the metallographic microscope was used to observe that the pattern was well formed ( Figure 9-Figure 14 Then, excellent lines were obtained by electron beam exposure and scanning electron microscopy ( Figure 15-16 Finally, through extreme ultraviolet exposure and scanning electron microscopy, relatively excellent lines were obtained ( Figure 17-Figure 18 ). It is worth noting that there are very few examples of pure metal oxide clusters being patterned in visible light experiments.
[0117] In addition, titanium alkoxide and benzoic acid derivatives were changed to synthesize four compounds, and visible light, electron beam and extreme ultraviolet lithography experiments were carried out (Comparative Examples 11-14). Unfortunately, Comparative Example 1 could not form a uniform film ( Fig.19 ), Comparative Examples 2-4 did not obtain ( Figure 20-22 ).
[0118] In summary, the free radical photoinitiator containing a carbonyl group disclosed in the present invention exhibits excellent performance in a photoresist composition. Whether in ultraviolet / visible light lithography, electron beam lithography or extreme ultraviolet lithography, the photoinitiator can significantly improve the sensitivity of metal oxygen clusters and metal oxide nanoparticle film-forming monomers and improve patterning efficiency. At the same time, the imaging quality and resolution of the pattern can also be improved. At the same time, the photoinitiator can also ensure the stability and integrity of the pattern during the development process, thereby meeting the demand for high-precision patterning in modern micro-nano manufacturing and semiconductor production.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A photoresist composition, characterized in that The photoresist composition comprises an organic solvent and titanium oxide nanoparticles, wherein the weight ratio of the titanium oxide nanoparticles in the composition is 1-30wt%, the weight ratio of the organic solvent in the composition is 70-99wt%, and the titanium oxide nanoparticles are formed by combining metal titanium alkoxide and benzoic acid or its derivatives.
2. The photoresist composition according to claim 1, characterized in that The structural formula of the titanium oxide compound nanoparticles is shown in general formula I, wherein: R' to R""" are each independently selected from one of n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, isopentyl and neopentyl; R1, R2, R3, R4, R5 are each independently selected from one of hydrogen, nitro, halogen, a hydrocarbon group having 1 to 8 carbon atoms, or a hydrocarbon group having 1 to 8 carbon atoms substituted by a hydrocarbonoxy group, a hydrocarbonamino group, or a dihydrocarbylamino group:
3. The photoresist composition according to claim 1, characterized in that The metal titanium alkoxide is selected from one or more of titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, titanium isobutoxide, titanium n-pentoxide, titanium isopentanol, and titanium neopentoxide; The structural formula of the benzoic acid or its derivatives is shown in general formula II: Wherein, R1, R2, R3, R4, and R5 are each independently selected from one of hydrogen, nitro, halogen, a hydrocarbon group having 1 to 8 carbon atoms, or a hydrocarbon group having 1 to 8 carbon atoms substituted by a hydrocarbonoxy group, a hydrocarbonamino group, or a dihydrocarbylamino group.
4. The photoresist composition according to claim 1, characterized in that The particle size of the titanium oxide nanoparticles is 1 to 3 nm.
5. The photoresist composition according to claim 1, characterized in that The weight ratio of the metal titanium alkoxide to benzoic acid or its derivative is 1-1.2:
1.
6. The photoresist composition according to claim 1, characterized in that The organic solvent is selected from one or more of toluene, o-xylene, m-xylene, p-xylene, m-trimethylbenzene, propylene glycol methyl ether acetate, propylene glycol methyl ether, chloroform, acetone, cyclopentanone, cyclohexanone, 4-methyl-2-pentanone, 2-heptanone, methanol, ethanol, n-propanol, isopropanol, butyl acetate, ethyl lactate, dimethyl sulfoxide and N,N-dimethylformamide.
7. A method for preparing the photoresist composition according to claim 1, characterized in that: The following steps are involved: (a) dissolving metal titanium alkoxide and benzoic acid or its derivative in an organic solvent I and mixing them uniformly; (b) reacting the mixture obtained in step (a) at 75-85° C. under an inert atmosphere; (c) cooling to room temperature, separating and drying the solid product to obtain titanium oxide nanoparticles, and then dissolving the solid product in an organic solvent to obtain a photoresist composition; Wherein: the organic solvent I is heptane and tetrahydrofuran, and the weight ratio of heptane to tetrahydrofuran is in the range of 0.6 to 2.0:
1.
8. A patterning method using the photoresist composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: A photoresist composition is applied on a substrate, and a photoresist film is formed by baking or drying at room temperature. The photoresist film is exposed to light and then placed in a developer to form a photolithographic pattern. The photolithographic exposure method is visible light lithography, electron beam lithography or extreme ultraviolet lithography.
9. The method for patterning a photoresist composition according to claim 8, characterized in that: The light source of the visible light lithography method is visible light with a wavelength of 365 to 600 nm and a dosage of 10 to 500 mJ·cm -2 The electron beam lithography method is to expose the electron beam using an electron beam exposure machine, with a dose of 50pC to 50000pC·cm -1 The light source of the EUV lithography method is EUV light with a wavelength of 13.5 nm and a dose of 5 to 500 mJ·cm -2 .
10. Use of the photoresist composition according to any one of claims 1 to 6 in the fields of micro-nano manufacturing, semiconductor production, biomedicine, and optical devices.